Primary Breast Burkitt's Lymphoma: A Case Report - Bautista, Deisy Areli Lárraga; Canché, Binui Jesús Kumul; Mendoza, María Elena Arroyo; Torres, Laura del Sagrario González; Martínez, Tamara Espinosa (British Journal of Healthcare and Medical Research, 2025)
We report the case of a 59-year-old Mexican woman who was treated in the emergency department (ED) on two occasions, the first one for a gastroenteritis episode, during which a tumor mass was found in the upper outer quadrant of her right breast along and ipsilateral axillary adenomegaly, both painful, with a three-month evolution. After the patient’s discharge, she was unable to continue the diagnostic protocol on an outpatient basis, as she was readmitted 15 days later due to a convulsive episode in conjunction with severe hyponatremia. Relevant prior findings to this admission included episodes of fever and a weight loss of eight kg. During the physical examination, the presence of the tumor was ratified, and an excisional biopsy was performed. On the sixth day of hospitalization, she began to experience progressive neurological deterioration. A cranial tomography revealed a hypodense lesion in the right occipital lobe of the brain. Due to the imminent need for cardiopulmonary resuscitation measures, the family's request was denied, and the patient passed away shortly after. Histopathological examination of the biopsy identified a lymphoid neoplasm with a diffuse growth pattern composed of medium-sized, monotonous, discohesive cells with evident nucleoli, frequent atypical mitosis, and abundant macrophages—findings suggestive of a Burkitt lymphoma, ratified six days after the death with immunohistochemical studies that identified positive CD20 and CD10, negative bcl-2 and CD3, and 90% for Ki-67 and 90% for MYC. The patient did not receive any type of chemotherapy.